PENGARUH CORPORATE SOCIAL RESPONSIBILITYTERHADAP KINERJA KEUANGAN, DENGAN LEVERAGE DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL (STUDI PADA PERUSAHAAN PERTAMBANGAN DI BURSA EFEK INDONESIA PADA PERIODE 2012 s.d 2013) - Rizal, Yenny; Agusti, Restu (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2017)
This research intends toexamine the influence of Corporate Social Responsibility onfinancial performance with leverage as control variables and examine the influenceof Corporate Social Responsibility to the financial performance of the company sizeas a control variable.The object of this research ismining company listed on theStock Exchange from 2012 to 2013.This research was conducted for 23companies.Analyctical model which used for this research to Multiple LinearRegression Analysis.Based on research concluded thatthe Corporate SocialResponsibility affect the earning per share. It can be proven by the secondhypothesis. And then, Corporate Social Responsibility affect the return on equity bycompany size as a control variable. This can be evidenced by the fifth hypothesis.